Spleen Volume Dynamics and Survival Outcomes in HCC Patients Undergoing Immune Checkpoint Inhibitors: A Retrospective Analysis - Fu X; Jiang S; Li Y; Guo Y; Gong B; Lou J; Li Y; Wang S; Sun Y; Ren Y; Chen Q; Yang L (Journal of Hepatocellular Carcinoma, 2025)
Xiaona Fu,1– 3,* Shanshan Jiang,1– 3,* Yi Li,1– 3,* Yusheng Guo,1– 3 Bingxin Gong,1– 3 Jie Lou,1– 3 Yanlin Li,4 Sichen Wang,5 Yuxin Sun,1– 3 Yi Ren,1– 3 Quan Chen,1– 3 Lian Yang1– 3 1Department of Radiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Provincial Clinical Research Center for Precision Radiology & Interventional Medicine, Wuhan, 430022, People’s Republic of China; 3Hubei Key Laboratory of Molecular Imaging, Wuhan, 430022, People’s Republic of China; 4Department of Radiology, the First People’s Hospital of Jiangxia District, Wuhan, 430200, People’s Republic of China; 5School of Life Science and Technology, Computational Biology Research Center, Harbin Institute of Technology, Harbin, 150001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quan Chen, Department of Radiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China, Email chenquan1230@126.com Lian Yang, Department of Radiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China, Email yanglian@hust.edu.cnPurpose: The spleen serves as an important immune organ which influences the anti-tumor immune response by modulating the immune microenvironment. This study investigated the prognostic impact of spleen volume (SV) on the survival in hepatocellular carcinoma (HCC) patients receiving immune checkpoint inhibitors (ICIs).Patients and Methods: This retrospective study included 224 HCC patients treated with ICIs, categorized into Higher and Lower SV groups by median SV and further into SV increased and Non-SV increased groups based on changes in SV at 3 months after ICIs. Kaplan-Meier curves and Cox regression models were used to evaluate the influence of SV and clinical indicators on progression-free survival (PFS) and overall survival (OS). Independent prognostic factors identified via multivariate analysis were incorporated into nomograms, with their accuracy assessed using concordance index (C-index), time-dependent receiver operating characteristic (ROC) and calibration curves. Restricted cubic spline (RCS) analysis was conducted to assess the relationship between baseline SV and survival.Results: The Higher SV and SV increased groups demonstrated shorter PFS and OS compared to the Lower SV and Non-SV increased groups, respectively. These results were consistent with different regimens in the Child A. The C-index of nomogram for PFS were 0.700 (0.678– 0.721) and OS 0.733(0.709– 0.757). The ROC and calibration curves confirmed robust discrimination and predictive accuracy of models. RCS analysis revealed a nonlinear association between baseline SV and survival risk, providing a more comprehensive overview of SV in relation to survival in HCC patients treated with ICIs.Conclusion: The baseline SV and its relative change at three months after treatment are expected to become routine imaging makers for predicting survival in HCC patients receiving ICIs, which consequently contributes to their clinical management.Keywords: spleen volume, hepatocellular carcinoma, immune checkpoint inhibitors, survival, nomogram